2009
DOI: 10.1038/icb.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Developing vaccines against minor capsid antigen L2 to prevent papillomavirus infection

Abstract: A subset of human papillomavirus (HPV) genotypes is responsible for ~5% of all cancer deaths globally, and uterine cervical carcinoma accounts for the majority of these cases. Their impact is greatest for women who do not have access to effective secondary preventive measures, and consequently over 80% of cervical cancer deaths worldwide occur in Developing nations. The understanding that persistent infection by this ‘oncogenic’ subset of HPV genotypes is necessary for the development of cervical carcinoma has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 128 publications
(419 reference statements)
1
58
0
2
Order By: Relevance
“…However, sequences at the C terminus of L2 have been demonstrated as membrane destabilizing and required for infection (21). Furthermore, transmembrane domain prediction software suggests that a highly conserved transmembrane domain might reside between residues 45 to 67 of HPV16 L2 (22), with equivalent regions in L2 sequences of all other types examined, but none in L1 or VP2 of the polyomaviruses MCV and BKV. Nevertheless, to date, we have failed to detect a consistent cleavage of L2 or L1 upon infection of HaCaT cells with HPV16 pseudovirions that could be blocked by ␥-secretase (or furin) inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, sequences at the C terminus of L2 have been demonstrated as membrane destabilizing and required for infection (21). Furthermore, transmembrane domain prediction software suggests that a highly conserved transmembrane domain might reside between residues 45 to 67 of HPV16 L2 (22), with equivalent regions in L2 sequences of all other types examined, but none in L1 or VP2 of the polyomaviruses MCV and BKV. Nevertheless, to date, we have failed to detect a consistent cleavage of L2 or L1 upon infection of HaCaT cells with HPV16 pseudovirions that could be blocked by ␥-secretase (or furin) inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In confirmation of this, animals immunized with the HPV L2 protein produced neutralizing antibodies for a broad HPV spectrum [50,51]. This observation contrasts sharply with the type-specific protection induced by L1 and suggests the possibility of a simple pan-HPV prophylactic vaccine, based on the L2 protein [49,52,53].…”
Section: A Pan-hpv Vaccinementioning
confidence: 83%
“…For example, HPV-31 and -33 are more commonly found than -18 in the Northeast and Midwest regions, while in the North, South and Southeast regions, HPV-18 appears as the second most prevalent type [45][46][47][48]. This clearly shows that there is a need to develop a second generation of prophylactic vaccines against HPV, with a larger spectrum of action [49].…”
Section: A Pan-hpv Vaccinementioning
confidence: 99%
“…Some studies have already shown the immunogenic potential of the L2 protein against papillomavirus infections, identifying neutralizing and tumor rejection epitopes. However, the main advantage of a vaccine using the L2 gene is the potential to induce a broad spectrum of neutralizing antibodies, possibly with immune cross-reactivity, i.e., L2 can confer immune protection against a range of papillomaviruses, including HPV (Karanam et al, 2009;Jagu et al, 2011). In the case of E5, the possibility of using the gene as a therapeutic vaccine against papillomavirus is still underexplored.…”
Section: Resultsmentioning
confidence: 99%
“…L2 protein is the minor viral capsid protein but is essential for papillomavirus infection. It is responsible for binding to a secondary viral receptor, thereby facilitating the exit from the endosome and the delivery of the viral genome to the nucleus (Karanam et al, 2009). …”
Section: Introductionmentioning
confidence: 99%